1972
DOI: 10.1111/j.1949-8594.1972.tb08919.x
|View full text |Cite
|
Sign up to set email alerts
|

“How Effective is the SCIS Science Program?”

Abstract: Research conducted at the University of Oklahoma in the Spring of 1971, has provided data from which one evaluation can be made of the elementary science curriculum developed by the Science Curriculum Improvement Study (SCIS) [2]. Since its origin in 1962, the project has invested over four million dollars in developing this new science curriculum [1]. Because of the large amount of public money invested and the fact that many schools are currently using the SCIS program, one would expect the availability of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The learning cycle is a sound instructional model that has been shown effective at a variety of grade levels (Weber & Renner, 1972;Purser & Rennet, 1983;Saunders & Shepardson, 1987;Stepans et al, 1983). For preservice teachers to successfully incorporate the use of the learning cycle with textbooks, methods classes should provide a good role model of this approach and ample time for students to practice using this instructional strategy.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The learning cycle is a sound instructional model that has been shown effective at a variety of grade levels (Weber & Renner, 1972;Purser & Rennet, 1983;Saunders & Shepardson, 1987;Stepans et al, 1983). For preservice teachers to successfully incorporate the use of the learning cycle with textbooks, methods classes should provide a good role model of this approach and ample time for students to practice using this instructional strategy.…”
Section: Resultsmentioning
confidence: 98%
“…The units of SCIS ~,ere organized around a specific activity-oriented teaching approach called the learning cycle (SCIS, 1974). In an evaluation of the SCIS program, the learning cycle was found to be a very effective teaching stmlcgy (Weber & Renner, 1972). Additional studies have also revealed that the approach can be effectively applied to other instructional materials (Purser & Rennet, 1983;Saunders & Shel> ardson, 1987;Stepans, Dyche, & Beiswenger, 1983).…”
Section: Indiana Universitymentioning
confidence: 93%
“…The Learning Cycle originated in an elementary science program called the Science Curriculum Improvement Study (SCIS). In an evaluation ofthe SCIS program, the Learning Cycle was found to be an effective teaching approach (Weber & Renner 1972).…”
Section: The Learning Cyclementioning
confidence: 99%
“…Ward & Yager, 1980;Mackay, 1971;Jungwirth, 1972;Rakow, Welch & Hueftle, 1984;Smith, 1978;Tobin & Capie, 1980;Welch, Klopfer, Aikenhead & Robinson, 1981;Yager and Yager, 1985), though there is evidence that both can be improved significantly if learning experiences are designed specifically to do so (Barnfield, Bethel & Lamb, 1977;Bowyer and Linn, 1978;Haukoos and Penick, 1983;Peterson, 1978;Weber and Renner, 1972). Some modern courses appear to lead to improved critical thinking and problem solving (Dillashaw and Okey, 1980;Padilla, Okey & Garrard, 1984;Seymour and Sutnam, 1973;Shaw, 1983), but there is little evidence that children can transfer these skills to situations outside the laboratory (Dreyfus & Jungwirth, 1980;Kamm, 1971;Saadeh 1973;Tabbron and Kerr, 1971).…”
mentioning
confidence: 99%